Elsevier's dictionary of information security in English, German, French and Russian (Elsevier, 2007)
This dictionary contains 13,000 terms with more than 4,000 cross-references used in the following fields: automation, technology of management and regulation, computing machine and data processing, computer control, automation of industry, laser technology, theory of information and theory of signals, theory of algorithms and programming, philosophical bases of cybernetics, cybernetics and mathematical methods